Through‐Thickness Electric Field Establishes Complex Molecular Architectures for Localized Liquid Secretion - Dongyu Zhang; Julia Nuijten; Jacques Peixoto; Danqing Liu (Advanced Science)
Abstract Localized liquid secretion, being an important process in nature such as the secretion of tears or mucus, has been an attractive point in developing biomimetic materials. However, precise localization remains challenging due to the cohesive and mobile nature of liquids. In this paper, light‐induced localized liquid secretion is demonstrated on the scale of tens of micrometers by a liquid crystal polymer coating with an alternating homeotropic‐planar alignment. The light responsiveness is achieved by the incorporation of azobenzene derivative. The localization is achieved by applying regional through‐thickness electric fields to the monomeric liquid crystals before polymerization. The polymerized coating preserves both homeotropic and planar alignment. Upon actuation, the liquid can be locally secreted from the homeotropic region while suppressed in the planar area. This method allows precise control over various secretion patterns based on different pre‐designed electrodes, which paves the way for the development of responsive devices in a multitude of fields, such as targeted drug delivery, tissue engineering, and microfluidic devices.